Supporting Characteristics of Soldier Piles for Foundation Pits under Rainfall Infiltration - Changxi Huang; Xinghua Wang; Min Zhang; Hao Zhou; Yan Liang (Advances in Civil Engineering)
The evolution of supporting characteristics of soldier piles for foundation pits under rainfall infiltration is described in this paper. Based on the Richards seepage equation and earth pressure theory considering the effect of intermediate principal stress of unsaturated soil, the approximate solution of permeability coefficient in unsaturated soil is developed using the Laplace integral transform and residue theorem. The transition of the boundary condition from flux boundary to head boundary is taken into account, and the rationality of the solution is verified. The safety factor of soldier piles’ stability against overturning is derived, and its displacements are obtained by the finite-difference method. The results show that the stability of soldier piles gradually decreases with rainfall duration, and the actual embedded depth of the pile should be greater than the minimum embedded depth specified by the design code. The displacement response of pile top lags behind the rainfall and increases later in the rainfall period. The hysteresis time is shortened with the increase of soil permeability. Considering moisture absorption, the effect of rainfall on the properties of retaining structure is limited for the homogeneous soils with low suction or permeability.